Synthesis and biological evaluation of 1, 3-diaryl pyrazole derivatives as potential antibacterial and anti-inflammatory agents. Issue 22 (15th November 2015) - Li, Ya-Ru; Li, Chao; Liu, Jia-Chun; Guo, Meng; Zhang, Tian-Yi; Sun, Liang-Peng; Zheng, Chang-Ji; Piao, Hu-Ri
Graphical abstract: Abstract: Three series of 1, 3-diaryl pyrazole derivatives bearing aminoguanidine or furan-2-carbohydrazide moieties have been synthesized, characterized and evaluated for antibacterial and anti-inflammatory activities. Most of the synthesized compounds showed potent inhibition of several Gram-positive bacterial strains (including multidrug-resistant clinical isolates) and Gram-negative bacterial strains with minimum inhibitory concentration values in the range of 1–64 μg/mL. Compounds6g, 6l and7l presented the most potent inhibitory activity against Gram-positive bacteria (e.g. Staphylococcus aureus 4220), Gram-negative bacteria (e.g. Escherichia coli 1924) and the fungus, Candida albicans 7535, with minimum inhibitory concentration values of 1 or 2 μg/mL. Compared with previous studies, these compounds exhibited a broad spectrum of inhibitory activity. Furthermore, compound7l showed the greatest anti-inflammatory activity (93.59% inhibition, 30 min after intraperitoneal administration), which was more potent than the reference drugs ibuprofen and indomethacin.